Determinants of farmers’ willingness to pay for improved cultivars of Macrotyloma geocarpum (harms) Maréchal and Baudet in Benin and Togo - Agossou, Aboègnonhou Chaldia Odette; N’Danikou, Sognigbé; Fassinou Hotègni, V. Nicodème; Kakpo, Thomas Ange; Coulibaly, Mariam; Oselebe, Happiness Ogba; Achigan-Dako, Enoch Gbènato (Frontiers in Sustainable Food Systems, 2023)
Introduction: Quality seed is essential to satisfy food demand. This is also true for neglected crops especially those that are economically valuable such as Kersting’s groundnut (Macrotyloma geocarpum), which holds the potential to improve farmer’s livelihood. In this study we assessed the attributes that drove Kersting groundnut’s farmers willingness to pay for improved seeds. Methods: A total of 567 respondents were selected in the Northern Guinea zone and Southern Sudanian production zones in Benin and Togo using the chain referral sampling and then interviewed with a semi structured questionnaire. Classification and regression trees, Ordinary Least Squared and Tobit regression were combined to assess the relationship between the socio- demographic variables and farmers’ Willingness to Pay (WTP) and Amount they are Willing to Pay (AWTP). Results and discussion: Results suggested that more than 90% of respondents involved in the production of Macrotyloma geocarpum were willing to access its improved seeds, including those who had already abandoned the cultivation of this crop due to constraints such as the very low seed yield of current cultivars, the difficulty to access seeds and the cultivation practices. The factors which affected the amount farmers are willing to pay included: the low yield of current cultivars used by farmers, the expected yield of the improved variety, which should be higher than one ton per ha (1 t.ha-1); the socio-linguistic group affiliation and the adoption level of improved agricultural technologies. The average amount fixed by seed companies that farmers were willing to pay for one kg of the improved seed was USD 5.35 but they have freely proposed to pay the amount of USD 4.63 to access one kg of improved seed. The white-seeded cultivar was the most appreciated by farmers and was the most cultivated in the Northern Guinean Zone whereas the cultivation of the colored-seeded (e.g., black-seeded) cultivars was mainly noted in the Southern Sudanian Zone. Further, the respondents elucidated seed yield improvement and disease management as their main research needs to help increase the production of the crop. The findings of this research will help refine Macrotyloma geocarpum improvement programs to release farmers-needed varieties.